SOME PALAEOZOIC 'PROTORTHOPTERA' ARE 'ANCESTRAL' ORTHOPTEROIDS: MAJOR WING BRACES AS CLUES TO A NEW SPLIT AMONG THE 'PROTORTHOPTERA' (INSECTA) - Bethoux O.; Nel A. (My University, 2004)
The Archaeorthoptera is an apomorphy-based supra-ordinal clade of insect that mainly comprises the extant order Orthoptera and the fossil orders Caloneurodea and Titanoptera. Our knowledge of this group is, however, incomplete because some taxa assigned to the paraphyletic group 'Protorthoptera' have not been accurately described. Here we describe or re-describe Carboniferous material assigned to Omalia macroptera Van Beneden & Coemans, 1867, Coselia palmiformis Bolton, 1922, Palaeomastax carbonis Handlirsch, 1904, Omaliella ramosa n. gen. & n. sp., Eoblatta robusta (Brongniart, 1885), Ctenoptilus elongatus (Brongniart, 1893) n. comb., Ischnoptera diaphanes n. gen. & n. sp., Protodiamphipnoa gaudryi (Brongniart, 1885), Cnemidolestes woodwardi (Brongniart, 1893), Ischnoneura oustaleti (Brongniart, 1885), Narkeminopsis eddi Whalley, 1979 and Bouleites latipennis Lameere, 1917. These taxa are all assigned to the Archaeorthoptera, based on the presence of characteristic features in their wing venation. A new system of homologies of the median system is proposed, which implies the loss of vein MP has occurred in some of these taxa. Our new data demonstrate the weakness of the previous specific, generic, familial and ordinal taxonomies.
Keywords: INSECTA; PTERYGOTA; ARCHAEORTHOPTERA; ORTHOPTERA; CARBONIFEROUS; Paleozoic::Carboniferous; Палеозой::Каменноугольная